Administration of Oral Therapy For Gonorrheal Urethritis Patients With Local Complications In Men: Case Reports - Citra Dwi Harningtyas (Journal of Agromedicine and Medical Sciences, 2017)
Urethritis gonorrhea is the most prevalent venereal disease today and can be found all over the world. Timeliness of treatment, correct selection of drugs with adequate doses can eliminate infections that affect the individual, prevent the development of complications, prevent further transmission and avoid germ resistance. This article reports, 24-year-old male patient with a diagnosis of gonore urethritis who came to polyclinic Skin and Veneral at Hospital Syaiful Anwar Malang. Patients come with complaints of pus out of the genitals without itching. Patients also complain of pain during urination, as well as urinating in small volume and often. On examination of external urethra urifisium area obtained ectropion, purulent discharge, and hyperemia macula. There is a lump and duh at the tip of the genitalia caused by inflammation of the paraurethral glands. From the investigation found diplococcus bacteria Gram negative intrasellular PMN. The causative therapy given is a single oral dose of Oral 400mg. Evaluation was done 3 days after treatment and improvement was obtained. Keywords: gonorrhea urethritis; oral urethritis therapy; uretritis gonorrhea complications